2020
DOI: 10.1109/tii.2019.2925023
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Shortcut Addition Algorithm With Particle Swarm for Multisink Internet of Things

Abstract: The Internet of Things (IoT) integrates a large number of distributed nodes to collect or transmit data. When the network scale increases, individuals use multiple sink nodes to construct the network. This increases the complexity of the network and leads to significant challenges in terms of the existing methods with respect to the aspect of data forwarding and collection. In order to address the issue, this paper proposes a Shortcut Addition strategy based on the Particle Swarm algorithm for multi-sink netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…An important problem in the IoT is to reduce the number of hops from the sensor to the sink. Reference [57] studied the modeling problem of small-world networks with multiple convergence points, and proposed a PSO-based novel shortcut addition algorithm for multi-sink IoT (SAPS). Each cluster is treated as a single aggregate network.…”
Section: Application Of Swarm Intelligence Algorithms In Other Iotsmentioning
confidence: 99%
“…An important problem in the IoT is to reduce the number of hops from the sensor to the sink. Reference [57] studied the modeling problem of small-world networks with multiple convergence points, and proposed a PSO-based novel shortcut addition algorithm for multi-sink IoT (SAPS). Each cluster is treated as a single aggregate network.…”
Section: Application Of Swarm Intelligence Algorithms In Other Iotsmentioning
confidence: 99%
“…Recently, the majority of the literature on PVEC have focused on allocating the resources of PVs [7,27]. Gu et al [13] propose a two-tier data center architecture that leverages the excessive storage resources in parking lots.…”
Section: Related Workmentioning
confidence: 99%
“…However, the selection of reward forms in incentive strategies needs to meet the different preferences of each task completers, it is difficult to achieve. Also, some researchers improve the quality of service of task completers by improving the characteristics [31] of crowdsourcing tasks. Guo et al [32] showed that the introduction of occasional breaks, such as playing games or reading comics, can improve task completers' quality of service.…”
Section: Mechanisms For Solving the Quality Of Service Dilemmamentioning
confidence: 99%